2022
DOI: 10.7326/m22-0803
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Performance of Centers for Disease Control and Prevention COVID-19 Community Levels as Leading Indicators of COVID-19 Mortality

Abstract: Notifying stakeholders, including the public, about the current community level of COVID-19 infection has become an integral part of the public health response to the epidemic. In a nationwide study, the ability of various metrics to predict community COVID-19 mortality risk was examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Alterative formulations of the CDC COVID-19 community levels may improve stability for medium risk level and would increase the number of countries in this grouping. We anticipate that these alternative metrics would have similar predictive performance of elevated mortality risk to current CDC metrics because of their similar definitions of high community levels [ 5 ]. However, prospective validation of their consistency and predictive value would be key to confirm their public health utility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterative formulations of the CDC COVID-19 community levels may improve stability for medium risk level and would increase the number of countries in this grouping. We anticipate that these alternative metrics would have similar predictive performance of elevated mortality risk to current CDC metrics because of their similar definitions of high community levels [ 5 ]. However, prospective validation of their consistency and predictive value would be key to confirm their public health utility.…”
Section: Discussionmentioning
confidence: 99%
“…A CDC Science Brief describing the design of these metrics reported that definitions of community levels were chosen to maximize predictive accuracy for disease burden over a 3-week window [ 4 ]. Moreover, a recent study has shown that the CDC metrics had moderate (∼70) positive predictive value of elevated COVID-19 mortality at county-level in the United States during the Delta and Omicron variant transmission periods [ 5 ].…”
mentioning
confidence: 99%
“…We defined “high mortality” as >1 death per 100,000 per week and “very high mortality” as >2 deaths per 100,000 per week. The lower threshold was defined in reference to peak mortality of other respiratory viruses (influenza and respiratory syncytial virus) during a severe season (7, 14). Let T M ∈ 1, 2 denote these mortality thresholds.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the indicators used in CDC Community Levels were selected because they correlated with ICU rates and mortality 3 weeks in the future (2). However, the thresholds for low, medium, and high did not correspond to specific future mortality rates (7), thus complicating the understanding of a “high risk” designation.…”
mentioning
confidence: 99%
“…5 While this approach addresses a major priority (prevention of severe disease and death), hospital-based data are not timely indicators of transmission, and are therefore inadequate for informing strategies that prevent severe outcomes. 19 Moreover, hospitalization data increasingly reflect a lack of access to care and a lack of uptake of boosters and antivirals among those at risk, making hospitalization data biased indicators of community transmission. Wastewater surveillance for SARS-CoV-2 has demonstrated a potential critical role in the timely detection of surges, 20 but wastewater metrics are challenging to standardize and gaps remain in contextualizing wastewater indicators with epidemiological data for policy decisions.…”
Section: Surveillance Gaps In Monitoring Transmission and Severitymentioning
confidence: 99%